2011
DOI: 10.1016/j.hkpj.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of pain, active range of motion, and disability in patients with acute nonspecific low back pain

Abstract: Many parameters are now used for investigations in clinical settings, such as pain, active range of motion (AROM), and disability, but it is not yet known which parameters are responsive in patients with acute nonspecific low back pain (LBP). This study aimed to investigate the responsiveness of pain, AROM, and disability in patients with acute nonspecific LBP. Fifty subjects were assessed for pain, AROM, and disability at baseline and after 6 weeks. The effect size (ES) was calculated for each parameter. Also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
6
1
1
Order By: Relevance
“…The findings of this study contradict those of Sakulsriprasert et al [39], who found a reduction in pain level as well as improvements in lumbar range of motion and functional status in a group of NSLBP patients who received conventional therapy versus a group that received lumbar mobilization in addition to conventional therapy. They concluded that Maitland's mobilization had no additional effect [39]. This variation could be explained by the onset of LBP in their study, which was conducted on individuals who had acute NSLBP.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of this study contradict those of Sakulsriprasert et al [39], who found a reduction in pain level as well as improvements in lumbar range of motion and functional status in a group of NSLBP patients who received conventional therapy versus a group that received lumbar mobilization in addition to conventional therapy. They concluded that Maitland's mobilization had no additional effect [39]. This variation could be explained by the onset of LBP in their study, which was conducted on individuals who had acute NSLBP.…”
Section: Discussioncontrasting
confidence: 99%
“…Relationships based on cross‐sectional data between spinal amplitude and disability were available for 69 studies and 5899 participants (Adamu et al, 2019; Alschuler et al, 2009; Alves et al, 2020; Ansari et al, 2014; Atya, 2013; Aure & Kvåle, 2022; Bayar et al, 2003; Bazzaz‐Yamchi et al, 2021; Caporaso et al, 2012; Carrasco‐Martínez et al, 2019; Christe et al, 2016; Coyle et al, 2017; de Brito Macedo et al, 2019; Demoulin et al, 2013; Deyo, 1986; Dubois et al, 2016; Duray et al, 2018; Ekedahl et al, 2010; Fehrmann et al, 2017; Felicio et al, 2017; Garcia et al, 2013; Grönblad et al, 1997; Grosdent et al, 2023; Grotle et al, 2004; Hidalgo et al, 2015; Hofste et al, 2021; Hrkać et al, 2022; Hurri et al, 1995; Ibrahim et al, 2019; Jette et al, 2016; Joshi et al, 2021; Kang et al, 1995; Karayannis et al, 2023; Kiran et al, 2017; La Touche et al, 2019; Larivière et al, 2022; Lee et al, 2001; Lenoir dit Caron et al, 2022; Loisel et al, 1998; Louw et al, 2015; Louw, Farrell, et al, 2017; Mannion et al, 2001; Matheve et al, 2019; Melikoglu et al, 2009; Miyachi et al, 2021; Nattrass et al, 1999; Nemcić et al, 2013; Nordstoga et al, 2019; Ostelo et al, 2003; Ozkaraoglu et al, 2020; Parks et al, 2003; Rainville et al, 1994; Sakulsriprasert et al, 2011; Sasani et al, 2008; Satpute et al, 2019; Scharovsky et al,…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [ 66 ] and Mobeen et al [ 72 ] observed an increase in lumbar ROM in the NSD therapy group after four and 2 weeks of treatment using a 3D motion analyzer and universal goniometer, respectively. None of the studies on the effects of NSD therapy assessed lumbar ROM through MMST, which is a highly reliable and valid test and an easy, fast, safe, and inexpensive test to be used clinically [ 73 ]. On the other hand, in most studies, straight leg raise (SLR) was assessed instead of directly measuring the lumbar ROM [ 3 , 21 , 30 , 31 , 64 , 71 ].…”
Section: Discussionmentioning
confidence: 99%